2012
DOI: 10.1039/c2cc34065h
|View full text |Cite
|
Sign up to set email alerts
|

Deep cavitand vesicles – multicompartmental hosts

Abstract: The synthesis and characterization of vesicles assembled from deep cavitands in water is reported. These vesicles act as hosts for three different types of guests: the cavitands bind small guest molecules, the bilayer attracts larger hydrophobic guests and the inner aqueous compartment contains hydrophilic molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…We began our work using resorcin [4]arene benzimidazole cavitands 1-3, calixarenes 4-6, and pillar[n]arenes 7 and 8, all of which are known to be hosts for various smallmolecule ammonium guests. Our screening partners have a guest-fluorophore conjugate structure (9)(10)(11)(12), where a small-molecule handle is attached to a fluorophore payload ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We began our work using resorcin [4]arene benzimidazole cavitands 1-3, calixarenes 4-6, and pillar[n]arenes 7 and 8, all of which are known to be hosts for various smallmolecule ammonium guests. Our screening partners have a guest-fluorophore conjugate structure (9)(10)(11)(12), where a small-molecule handle is attached to a fluorophore payload ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…[9] New hosts have emerged that are capable of self-micelle formation and compartmentalization of payloads. [10] Resorcinarenes have also formed ion channels in lipid environments. [11] This body of work has encouraged us to apply these results to cellular systems; it has been shown that resorcinarene cavitands can promote the endocytosis of fluorescein, so long as a complementary choline handle is attached.…”
Section: Introductionmentioning
confidence: 99%
“…For the NP synthesis, deionised (DI) water was purified by using a Millipore Milli‐Q RG ultrapure water system. Pyridine‐2‐carbohydrazide, [Fe(py) 4 (NCBH 3 ) 2 ], thioctic acid N ‐hydroxysuccinimide (NHS) ester and 2,5,8,11,14‐pentaoxaheptadecan‐17‐oic acid were synthesised according procedures reported in the literature. 1‐Pyrene carboxylic acid NHS ester was prepared by slight modification of a previously reported procedure, with 9:1 CH 2 Cl 2 /ethyl acetate rather than neat CH 2 Cl 2 as the eluting solvent during purification by column chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…Resorcin [4]arenes are synthetic organic compounds able to form a hemispherical structure with a diameter of ca. 10 Å at the upper rim and a hydrophobic cavity with an internal volume of 350 Å 3 that can accommodate many organic molecules [10]. These macrocycles are synthesized starting from resorcinol or 1,2,3-trihydroxyphenol and an appropriate aldehyde, which addresses the chemical characteristics of the lower rim [11].…”
Section: Catalysis Into Resorcinarene Hexameric Capsulesmentioning
confidence: 99%